The Timurid Empire: an efficient public safety system of a great power (a comprehensive historical and legal analysis) (Eurasian Journal of Humanities and Social Sciences, 2024)
This article is dedicated to a comprehensive study of the public safety system in the Timurid Empire. The analysis examines historical and legal aspects that allowed Timurid to create an effective and stable state governance system. Using historical and legal methods, the authors analyze key elements of the public safety system, including legal norms, administrative measures, and their implementation. The article's conclusions emphasize the significance of Timurid's historical experience for understanding the evolution of legal institutions and public safety management in contemporary contexts.